Identification and characterization of a critical loop for the high activity of alginate lyase VaAly2 from the PL7_5 subfamily - Du, Muxuan; Li, Xue; Qi, Weipeng; Li, Yingjie; Wang, Lushan (Frontiers in Microbiology, 2024)
As the major component in the cell wall of brown algae, alginates are degradable by alginate lyases via β-elimination. Alginate lyases can be categorized into various polysaccharide lyase (PL) families, and PL7 family alginate lyases are the largest group and can be divided into six subfamilies. However, the major difference among different PL7 subfamilies is not fully understood. In this work, a marine alginate lyase, VaAly2, from Vibrio alginolyticus ATCC 17749 belonging to the PL7_5 subfamily was identified and characterized. It displayed comparatively high alginolytic activities toward different alginate substrates and functions as a bifunctional lyase. Molecular docking and biochemical analysis suggested that VaAly2 not only contains a key catalyzing motif (HQY) conserved in the PL7 family but also exhibits some specific characters limited in the PL7_5 subfamily members, such as the key residues and a long loop1 structure around the active center. Our work provides insight into a loop structure around the center site which plays an important role in the activity and substrate binding of alginate lyases belonging to the PL7_5 subfamily.